The effect of a short educational intervention in social insurance medicine: A randomized controlled trial - Linda Lännerström; Inger K. Holmström; Thorne Wallman (Wiley, 2020)
Abstract Aim To evaluate the effect of an educational intervention in social insurance medicine with Registered Nurses. Design Randomized controlled trial. Methods The trial was performed in 20 primary healthcare centres in Central Sweden. The centres were randomly assigned as intervention or control. All Registered Nurses working with telephone nursing at the centres were invited (N = 114); out of these 100 agreed to participate and responded to a questionnaire at the beginning and end of the trial. Fourteen questions in the questionnaire dealt with professional background and were used as exposure variables and were analysed using nominal logistic regression. Results Registered Nurses in the centres randomly assigned for the intervention experienced handling sick leave questions as less problematic after the intervention than those in the control group. This indicated that the intervention was associated with a positive effect. However, due to the rather small study population, the effect was inconclusive.